History of Friedrich II of Prussia $1 (BVolume 11s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 11" by Thomas Carlyle is part of a six-volume biography published between 1858 and 1865. This monumental work chronicles the life of Frederick the Great, the Prussian king whom Carlyle considered heroic material for an epic. After thirteen years of painstaking research, including battlefield tours across Germany, Carlyle produced what contemporaries called his grandest achievement$1 (Ba vivid portrait blending military history, political analysis, and literary genius that brings eighteenth-century Prussia dramatically to life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786